HUBUNGAN LAMA TIDUR DENGAN PERUBAHAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI POSYANDU LANSIA DESA KARANG AREN - noviani, okti; -, handoyo; ANS, safrudin (Jurnal Ilmiah Kesehatan Keperawatan, 2011)
Sleep as a basic human need is influenced by various factors such as physiological and psychological factors and lifestyle. One of physiological factors is the instability of vital signs such as hypertension. In general, sleep disturbances become more frequent and very disturbing experience in line with the aging process, so the elderly often experience sleep quality disorder. The objective of this study is to prove the correlation between sleep duration with blood pressure change of the elderly people with hypertension in POSYANDU (health center) for elderly in Karang Aren Village. This study uses a quantitative correlation with an observational approach to pre and post test design. The data were analyzed by using t-test and product moment correlation. There were 30 respondents taken as the samples with inclusion and exclusion criteria and they were taken by random sampling technique. Research finding showed that the respondents who were based on sleep duration; minimum sleep duration was 5 hours and maximum sleep duration was 7 hours. The average sleep duration was 8.5 hours. Changes in blood pressure for blood pressure systole p-value = 0039 and the diastolic blood pressure p-value = 0016 at 0.05 confidence level.  Meant there were significant changes in blood pressure; in systole there was an increase and in diastole there was a decrease. The correlation between sleep duration with changes in blood pressure; systole with sleep duration = (sig) 0.727> 0.05 and diastole with sleep duration (sig) 0.679> 0.05, so that correlation between the two variables was not significant. There was significant differences before and after sleeping period how ever there was no correlation between sleep duration with blood pressure change of the elderly people with hypertension in POSYANDU (health center) for elderly in Karang Aren Village   Keywords      : Sleep duration, blood pressure changes, elderly with hypertension.